De l’usager consommateur à l’habitant réaménageur - Martin Minost (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This research aims at questioning the practices of appropriation of foreign-style housing by Chinese families in the neighbourhood of Thames Town, on the outskirts of Shanghai. Being dwellings identified as architectural copies, the analyses produced on these places have generally focused on the spatial form. The residential buildings of Thames Town have then been considered as inauthentic pastiches, denying the inhabitants any competence in giving them their own meaning. Our analysis reveals on the contrary the involvement of the residents in adapting the space for their own domestic practices. Far from being passive consumers of an illusory image of foreign lifestyles, they appropriate the space. The transformations carried out show that the dwelling is a resource and is a central element of their social trajectory. Through their appropriations and the production of a distinct domestic comfort, they express an experience of social liberation.